The Effectiveness of the Use of Virtual Laboratory in Physics Learning on the Concept Understanding and Critical Thinking Ability of High School Students - Siti Nurhabibah Hutagalung; Melda Panjaitan (Edumaniora : Jurnal Pendidikan dan Humaniora, 2026)
This study aims to analyze the effectiveness of using a virtual laboratory in physics learning on the conceptual understanding and critical thinking skills of high school students. The research method used was a quasi-experimental with a nonequivalent control group design. The research subjects consisted of two grades of XI MIPA in a public high school, with one class as an experimental class implementing physics learning using a virtual laboratory and one class as a control class using conventional learning. The research instruments included a conceptual understanding test and a critical thinking ability test that had been validated by experts. Data were analyzed using a normality test, a homogeneity test, and a t-test. The results showed that there were significant differences in conceptual understanding and critical thinking skills of students between the experimental and control classes (p < 0.05). Thus, the use of a virtual laboratory is effective in improving the quality of physics learning. The results of this study are expected to be an alternative solution for technology-based physics learning in high schools.